Post-Sekulerisme Islam Populis di Indonesia - Mujibuddin, M; Zuliana, Rina (JSW (Jurnal Sosiologi Walisongo), 2019)
This article explores the phenomenology of post-secularism in Indonesia. Populist Islamic movement strike for islamization public sphere as a sign of post-secularism in Indonesia. The islamization proceeded both in government dan the public sphere. These phenomena show that the community of urban Muslims can?t leave religious aspects in the public sphere. This research uses the qualitative-description method and library research models. The first result of this research shows that Islamic populism is coming from the urban Muslim middle class who have access to the modern world. Second, the populist Islamic movement who did islamization of the public sphere shows the strengthening of religion's role in the public sphere.